Air stable copper-silver core-shell submicron particles: Synthesis and conductive ink formulation - Pajor-Świerzy, Anna; Farraj, Yousef; Kamyshny, Alexander; Magdassi, Shlomo (Colloids and surfaces. A, Physicochemical and engineering aspects, 2017)
[Display omitted] •The air-stable Cu@Ag particles were synthesized.•The conductive inks containing Cu@Ag particles with optimal coating characteristics were formulated.•Metallic Cu@Ag films with conductivity as high as 16% of bulk copper were obtained. We report on the synthesis of copper-silver core-shell (Cu@Ag) particles with about 1μm-diameter Cu core coated with a thin (∼20nm) silver shell, for application in printed electronics as low cost conductive ink. The process is based on using the environmentally friendly sodium formaldehyde sulfoxylate dehydrate as a reducing agent for copper ions and two types of polymeric stabilizers (nonionic PVP and anionic PAA). The formation of core-shell particles is followed by transmetallation reaction on the surface of the Cu particles, where copper atoms function as the reducer for silver ions. Characterization of the submicron particles by SEM, EDS and XRD confirm the core-shell structure. The resulting Cu@Ag particles enable overcoming a major challenge in copper ink, their rapid oxidation in air. It was found that ink formulations based on propylene glycol as the liquid vehicle and containing a silicone based wetting agent possesses the optimal characteristics (wetting, sintering) for printing on a glass substrate. To obtain conductive metallic structures, thermal sintering of metallic patterns was used. The Cu@Ag coating are stable to oxidation for at least 6 months at room temperature, and also during sintering process which is carried out at temperatures up to 250°C. The conductivity of Cu@Ag coatings after sintering at 250°C was high, 16% of that for bulk copper.